2020
DOI: 10.1038/s41467-020-15942-1
|View full text |Cite
|
Sign up to set email alerts
|

Labeled oxytocin administered via the intranasal route reaches the brain in rhesus macaques

Abstract: Oxytocin may have promise as a treatment for neuropsychiatric disorders. Its therapeutic effect may depend on its ability to enter the brain and bind to the oxytocin receptor. To date, the brain tissue penetrance of intranasal oxytocin has not been demonstrated. In this nonhuman primate study, we administer deuterated oxytocin intranasally and intravenously to rhesus macaques and measure, with mass spectrometry, concentrations of labeled (exogenously administered) and endogenous oxytocin in 12 brain regions tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 43 publications
6
92
0
Order By: Relevance
“…Although the passage of IN OXT via the blood-brain barrier is still under debate [109] numerous reports in both rodents [151,152] monkeys [153] and humans [154,155] indicate the delivery of IN OXT into the brain in sufficient amounts. Recently, deuterated OXT has been detected in the CSF [153] and various brain tissues, including orbitofrontal cortex, thalamus, and striatum of macaques [156]. In line, a recent study of Paloyelis et al addressed an important question regarding intracerebral effects of IN OXT and showed changes in regional blood flow in the human brain [157].…”
Section: Translational Perspectivesmentioning
confidence: 81%
“…Although the passage of IN OXT via the blood-brain barrier is still under debate [109] numerous reports in both rodents [151,152] monkeys [153] and humans [154,155] indicate the delivery of IN OXT into the brain in sufficient amounts. Recently, deuterated OXT has been detected in the CSF [153] and various brain tissues, including orbitofrontal cortex, thalamus, and striatum of macaques [156]. In line, a recent study of Paloyelis et al addressed an important question regarding intracerebral effects of IN OXT and showed changes in regional blood flow in the human brain [157].…”
Section: Translational Perspectivesmentioning
confidence: 81%
“…In its classic nine–amino acid form, it was traditionally argued that oxytocin did not readily cross the blood-brain barrier ( Leng and Ludwig, 2016 ). However, in studies done in monkeys, intranasally administered oxytocin labeled with deuterium was detected in cerebrospinal fluid ( Lee et al, 2018 ) and in brain regions where oxytocin activity influences motivated behaviors ( Lee et al, 2020 ). This argument also is diminished by recent awareness of the capacity of RAGE to act as an oxytocin-binding protein facilitating the transport of oxytocin across the blood-brain barrier and through other tissues ( Yamamoto and Higashida, 2020 ).…”
Section: Methods For Administering Oxytocin or Stimulating The Oxmentioning
confidence: 99%
“…concomitant medication treatment) instead. PK data in primates suggests that exogenously administered oxytocin leads to minimal and short lived elevations in plasma oxytocin which reduces the risk for drug interactions [96]. The most relevant interactions will be concomitant medications that impact the serotonin or dopamine systems, both of which interact with the oxytocin system [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…This measure was adapted from the Safety Monitoring Uniform Report Form [95,96] and allowed for continuous monitoring of adverse events from the initial visit. Medical and behavioral conditions were assessed at each visit and those that were present at screening and/or baseline were considered treatment-emergent if their severity increased significantly after the participant had taken at least one dose of the study treatment.…”
Section: Systematic Longitudinal Adverse Events Scale (Slaes)mentioning
confidence: 99%